Guerrilla advertising cases study in public transport - Jarašūnienė, Aldona; Išoraitė, Margarita (Business: Theory and Practice, 2024)
Guerrilla marketing in public transport is distinguished by the fact that it usually avoids traditional advertising methods such as television commercials or newspaper ads. Guerrilla campaigns in public transport focus on creative tactics to surprise the public and generate buzz about the brand. These campaigns often use non-traditional methods to draw attention to the brand in question. Guerrilla campaigns can be useful for businesses looking to gain an edge over their competitors. The partisan campaigns tend to get more media attention than traditional methods because they are seen as new or unexpected. These campaigns can create excitement and anticipation for your product or service, which can help increase sales. The subject of this paper is a case study of Guerrilla advertising in public transport. The aim of the paper is to assess the usefulness of Guerrilla advertising in promoting the attractiveness of public transport. The paper discusses the analysis of scientific literature, presents the Guerrilla marketing concept, type and tools, advantages and disadvantages. Traditional and Guerrilla marketing, research methodology comprising case study and quantitative research method, based on the results of the analysis of the scientific literature and the result of the research suggestions are made. Cases of partisan marketing in public transport are rarely studied in the scientific literature.